A Screening Test for HLA-B∗15:02 in a Large United States Patient Cohort Identifies Broader Risk of Carbamazepine-Induced Adverse Events - Fang, Hua; Xu, Xiequn; Kaur, Kulvinder; Dedek, Matthew; Zhu, Guang-dan; Riley, Bae J.; Espin, Frank G.; Del Tredici, Andria L.; Moreno, Tanya A. (Frontiers in Pharmacology, 2019)
Purpose HLA-B*15:02 is strongly associated with life-threatening severe skin hypersensitivity reactions in patients treated with carbamazepine and structurally-related medications. FDA-approved labeling recommends HLA-B*15:02 screening before carbamazepine therapy in patients of Asian ancestry. In this study, we aimed to a) identify a direct method for screening HLA-B*15:02, and b) evaluate prevalence in a large cohort of United States (US) patients. Methods Candidate genetic markers were identified by mining public data. Association was tested in 28,897 individuals by comparing SNP results with high-resolution HLA typing. Retrospective analysis of de-identified SNP and ethnicity data from 130,460 individuals was performed to evaluate the ethnic distribution of HLA-B*15:02 in the US. Results 28,897 US individuals showed 100% concordance between HLA-B*15:02 and the minor allele of rs144012689 (100% sensitivity/99.97% specificity). Retrospective analysis of 160 positive individuals (66 with physician-reported ethnicity) notably included 28 Asians (42%), 15 African Americans (22%), 11 Caucasians (17%), 2 Hispanics (3%), and 10 ‘Other’ (15%). Conclusions Screening US patients for HLA-B*15:02 without ethnicity-based preselection identifies more than twice the number of carriers at risk of carbamazepine-related adverse events than screening patients of Asian ancestry alone. Risk assessment based on ethnicity assumptions may not identify a large portion of at-risk patients in the ethnically-diverse US population.